(untitled) (International Journal of Engineering and Computer Science, 2017)
In a Grid connected three-phase photovoltaic (PV) system, there is double-frequency power mismatch existed between the dc input and ac output. The double-frequency ripple (DFR) energy needs to be buffered by passive network. Otherwise, the ripple energy will flow into the input side and adversely affect the PV energy harvest. In a conventional PV system, electrolytic capacitors are usually used for this purpose due to their high capacitance. However, electrolytic capacitors are considered to be one of the most failure prone components in a PV inverter. In this project, a capacitance reduction control strategy is proposed to buffer the DFR energy in three-phase Z-source/quasi-Z-source inverter applications. Without using any extra hardware components, the proposed control strategy can significantly reduce the capacitance requirement and achieve low input voltage DFR. Consequently, highly reliable film capacitors can be used. The increased switching device voltage stress and power loss due to the proposed control strategy will also be discussed. The proposed system is simulated in MATLAB/Simulink platform.